2016
DOI: 10.1056/nejmoa1505067
|View full text |Cite
|
Sign up to set email alerts
|

Weekly vs. Every-3-Week Paclitaxel and Carboplatin for Ovarian Cancer

Abstract: BACKGROUND A dose-dense weekly schedule of paclitaxel (resulting in a greater frequency of drug delivery) plus carboplatin every 3 weeks or the addition of bevacizumab to paclitaxel and carboplatin administered every 3 weeks has shown efficacy in ovarian cancer. We proposed to determine whether dose-dense weekly paclitaxel and carboplatin would prolong progression-free survival as compared with paclitaxel and carboplatin administered every 3 weeks among patients receiving and those not receiving bevacizumab. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
244
1
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 318 publications
(257 citation statements)
references
References 35 publications
7
244
1
5
Order By: Relevance
“…When patients did not receive bevacizumab, a subgroup analysis of the GOG 262 trial showed a significant increase in PFS in favour of weekly paclitaxel compared with 3-weekly. When receiving bevacizumab, no differences in PFS were shown 199. As this subgroup analysis was not pre-planned and only performed on 16% of the study population, weekly paclitaxel should not be regarded as a substitution for bevacizumab.…”
Section: Resultsmentioning
confidence: 95%
“…When patients did not receive bevacizumab, a subgroup analysis of the GOG 262 trial showed a significant increase in PFS in favour of weekly paclitaxel compared with 3-weekly. When receiving bevacizumab, no differences in PFS were shown 199. As this subgroup analysis was not pre-planned and only performed on 16% of the study population, weekly paclitaxel should not be regarded as a substitution for bevacizumab.…”
Section: Resultsmentioning
confidence: 95%
“…In subgroup analysis the OS benefit was not seen for stage IV patients (dose dense 36 months versus conventional 33 months, p = 0.76). Further, dose-dense weekly paclitaxel studies (GOG #262 [76] and MITO-7 [77]) could also not demonstrate a significant benefit for the dose-dense regimens. There is no robust clinical data on efficacy of intra-peritoneal (IP) therapy in stage IV patients.…”
Section: Chemotherapymentioning
confidence: 94%
“…As noted above, these post hoc results must be interpreted with caution, and larger prospective studies are needed. 1 found a marginal benefit of dose-dense (weekly) chemotherapy over standard chemotherapy in a group of 112 women with ovarian cancer who did not receive bevacizumab, a subgroup that represents a mere 16% of the whole. The use of progressionfree survival, instead of overall survival, in trials of ovarian-cancer therapies will exaggerate the benefit of a therapy that delays progression but has no effect on survival.…”
Section: Doi: 101056/nejmc1602671mentioning
confidence: 99%
“…In our recent analysis of data from a large administrative U.S. database (the Healthcare Cost and Utilization Project National Inpatient Sample), we found remarkable similarity between patients with dilated cardiomyopathy and those with peripartum cardiomyopathy in terms of demographic and clinical characteristics and patient outcomes in pregnancy during the hospitalization for delivery. 1 Approximately 30% of the women in each cohort were black, and the two cohorts had similarly elevated rates of death, heart failure, arrhythmias, and preeclampsia spectrum disorders. Perhaps some of the patients (mis)classified as having peripartum cardiomyopathy were women with an asymptomatic dilated cardiomyopathy before pregnancy, and the hemodynamic demands of pregnancy worsened the degree of left ventricular dysfunction, leading to clinical heart failure.…”
Section: Doi: 101056/nejmc1602671mentioning
confidence: 99%
See 1 more Smart Citation